FENOMENA PEMAHAMAN DAN PENERAPAN HAKIKAT MAKNA KATA KEJAHATAN DAN PELANGGARAN DALAM PERKEMBANGAN HUKUM - Hamsir Hamsir (Universitas Islam Negeri Alauddin Makassar, 2020)
The word crime and violation in the legal phenomenon of society experiences distortion when reviewing sanctions from the act. The word crime means that sanctions are classified as severe, whereas violations are assumed to contain mild sanctions. In further legal developments, legal acts / legal events or offenses are identified with just one word, namely